A diploid wheat TILLING resource for wheat functional genomics - Rawat, Nidhi; Sehgal, Sunish K.; Joshi, Anupama; Rothe, Nolan; Wilson, Duane L.; McGraw, Nathan; Vadlani, Praveen V.; Li, Wanlong; Gill, Bikram S. (My University, 2012)
Background: Triticum monococcum L., an A genome diploid einkorn wheat, was the first domesticated crop. As a diploid, it is attractive genetic model for the study of gene structure and function of wheat-specific traits. Diploid wheat is currently not amenable to reverse genetics approaches such as insertion mutagenesis and post-transcriptional gene silencing strategies. However, TILLING offers a powerful functional genetics approach for wheat gene analysis. Results: We developed a TILLING population of 1,532 M[subscript 2] families using EMS as a mutagen. A total of 67 mutants were obtained for the four genes studied. Waxy gene mutation frequencies are known to be 1/17.6 - 34.4 kb DNA in polyploid wheat TILLING populations. The T. monococcum diploid wheat TILLING population had a mutation frequency of 1/90 kb for the same gene. Lignin biosynthesis pathway genes- COMT1, HCT2, and 4CL1 had mutation frequencies of 1/86 kb, 1/92 kb and 1/100 kb, respectively. The overall mutation frequency of the diploid wheat TILLING population was 1/92 kb. Conclusion: The mutation frequency of a diploid wheat TILLING population was found to be higher than that reported for other diploid grasses. The rate, however, is lower than tetraploid and hexaploid wheat TILLING populations because of the higher tolerance of polyploids to mutations. Unlike polyploid wheat, most mutants in diploid wheat have a phenotype amenable to forward and reverse genetic analysis and establish diploid wheat as an attractive model to study gene function in wheat. We estimate that a TILLING population of 5, 520 will be needed to get a non-sense mutation for every wheat gene of interest with 95% probability.
Citation: Rawat, N., . . . & Gill, B. (2012). A diploid wheat TILLING resource for wheat functional genomics. BMC Plant Biology, 12(1), 205. https://doi.org/10.1186/1471-2229-12-205
Keywords: TILLING; Reverse genetics; Triticum monococcum; Mutation frequency; Waxy; Lignin